The history and current status of surgery in the treatment of laryngeal cancer - Cocek, Ales (Acta medica (Hradec Kralove), 2008)
The roots of surgery of the larynx reach into the 19th century. After the gaining of initial experiences, a period of radical surgery followed when most tumours were treated with a total laryngectomy. The middle of the 20th century can be characterised as a period of partial laryngectomies. The mutilation of patients caused by a total laryngectomy was and is one of the main impulses that led to the development of the current phase--combined treatment (radiotherapy, systematic cytostatic chemotherapy, biological treatment, surgery as an emergency treatment). The aim is to treat carcinoma of the larynx without the actual removal of the larynx itself and with the same oncological results as would be reached in cases treated with a total laryngectomy. Despite the development of non-surgical methods, surgery of carcinoma of the larynx remains a significant part of the treatment protocol. This work covers the development of surgery of carcinoma of the larynx from a historical point of view; it also describes current types of operations and discusses the position of surgery in today's treatment algorithm.
Keywords: nádory hrtanu; Laryngeal Neoplasms; Humans; lidé; laryngektomie; Laryngectomy